2006
DOI: 10.1038/sj.mp.4001943
|View full text |Cite
|
Sign up to set email alerts
|

A proteomic study of serum from children with autism showing differential expression of apolipoproteins and complement proteins

Abstract: Modern methods that use systematic, quantitative and unbiased approaches are making it possible to discover proteins altered by a disease. To identify proteins that might be differentially expressed in autism, serum proteins from blood were subjected to trypsin digestion followed by liquid chromatography-electrospray ionization-mass spectrometry (LC-ESI-MS) on time-of-flight (TOF) instruments to identify differentially expressed peptides. Children with autism 4-6 years of age (n = 69) were compared to typicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
115
1
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(127 citation statements)
references
References 95 publications
(109 reference statements)
10
115
1
1
Order By: Relevance
“…Indeed, preliminary putative biomarkers have been identified in human blood sera taken from people with ASDs. For example, alterations in complement proteins [40][41][42] as well as in apolipoproteins, may be present [13,38,40]. Corbett et al [40] found that five peptide components corresponding to four known proteins (Apolipoprotein (apo) B100, Complement Factor H Related Protein (FHR1), Complement C1q and Fibronectin 1 (FN1)) had a MASCOT score of 30 or greater for autism compared to controls.…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, preliminary putative biomarkers have been identified in human blood sera taken from people with ASDs. For example, alterations in complement proteins [40][41][42] as well as in apolipoproteins, may be present [13,38,40]. Corbett et al [40] found that five peptide components corresponding to four known proteins (Apolipoprotein (apo) B100, Complement Factor H Related Protein (FHR1), Complement C1q and Fibronectin 1 (FN1)) had a MASCOT score of 30 or greater for autism compared to controls.…”
Section: Autism Spectrum Disorder (Asd)mentioning
confidence: 99%
“…As stated earlier in this manuscript, preliminary putative biomarkers have been identified in blood and saliva taken from individuals from other neurodevelopmental disorders, for example, idiopathic ASD. To give one example of putative biomarker identification, in human blood sera taken from people with ASDs, alterations in complement proteins [40][41][42] as well as in apolipoproteins, may be present [5,40]. Proteomic analysis of SLOS biomarkers has the potential to reveal new information about the disorder.…”
Section: Smith Lemli Opitz Syndromementioning
confidence: 99%
“…Studies have found increased levels of proteins involved in synapse formation, such as brain-derived neurotrophic factor (BDNF) and glial fibrillary acidic protein (GFAP) in ASD samples (Chauhan et al, 2011;Correia et al, 2010;Fatemi et al, 2002;Riikonen, 2003;Schwarz et al, 2011;Thanseem et al, 2012). Proteomic analyses have also found altered levels of immune system-regulating proteins, such as apolipoprotein in the cerebrospinal fluid and blood of individuals with ASD compared to controls (Corbett et al, 2007;Molloy et al, 2006;Woods et al, 2012;Zimmerman et al, 2005). Proteins show great promise as useful biomarkers for ASD, but large-scale replications are needed.…”
Section: Molecular Datamentioning
confidence: 99%
“…The ToM deficit is associated with processing of non-verbal sounds [10], human voices [8], touching [21], eye contact [17] and facial information [1,6]. Individuals with autism often exhibit impaired processing of emotions [14] mani-fested in the form of increased stress and anxiety [5,15]. As a result, children with autism regularly engage in stereotyped ritualistic behaviours and have difficulties initiating activities to share interests and cooperate with others.…”
Section: Introductionmentioning
confidence: 99%